DAMPAK FENOMENA EL NINO TERHADAP PENDAPATAN USAHATANI DAN POLA TANAM PETANI PADI DI KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Tri Nugroho; Zainal Abidin; Lina Marlina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
The purposes of this research are to analyze the impact of El Nino phenomenon in 2015 on rice farming income and on cropping pattern of farmers and to figure out mitigation efforts of farmers to anticipate the impact of the phenomenon. This research was conducted in two villages in Natar Subdistrict South Lampung Regency in August - November 2016. They are Pancasila Village which represents a pump irrigation area and Negararatu Village represents a technical irrigation area. Respondents were 76 rice farmers who were chosen simply randomly. The study used a quantitative descriptive analysis method. The study showed that El Nino phenomenon had no effect on farming income, and on cropping pattern.  Farmers mitigated by increasing the costs of water pump.Key words: cropping pattern, el Nino, farming income, mitigation